Author's method of securing the screen of the mobile device. - Iwaniuk, Grzegorz (Journal of Computer Sciences Institute, 2018)
With the development of mobile device technology, the need to protect these devices from unauthorized access is increasing. Currently, there are common methods of unlocking devices whose operation consists in reading the pattern or the password entered by the user. The article presents the creation of an original method of screen protection of a mobile device and its comparison with commonly used screen locking methods.